Double Vision : a Novel. - Garrett, George, 1929-2008 (Deep South books., 2004)
A shotgun marriage of fact and fiction by one of the most highly regarded writers and teachers of our time. A writer named George Garrett, suffering from double vision as a result of a neurological disorder, is asked to review a recent, first biography of the late Peter Taylor, a renowned writer who has been his long-time friend and neighbor in Charlottesville. Reflecting on their relationship, Garrett conceives of a character€"not unlike himself€"a writer in his early 70s, ill and suffering from double vision, named Frank Toomer. He gives Toomer a neighbor, a distinguished short story write